2016
DOI: 10.1080/19397038.2015.1136361
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of end-of-life terminology in the carbon fiber reinforced plastic industry

Abstract: While many studies and reviews into the practices conducted by industry and academia to recycle and remanufacture carbon fiber reinforced plastic (CFRP) exist, to date no investigation exists which regards the correctness of the use of terms recycling and remanufacturing. As such, this paper seeks to analyse the CFRP reuse industry's attempt to recycle and remanufacture manufacturing waste CFRP and end of life (EOL) CFRP with an emphasis on the terminology used to describe these practices. Firstly, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Several definitions of “reuse” are provided in legislation (e.g. EU, 2002, EU, 2008), standards (ISO, 2002, BSI, 2009) and scientific articles (King et al., 2006, Paterson et al., 2016).…”
Section: Towards a Classification Of Different Types Of Reusementioning
confidence: 99%
“…Several definitions of “reuse” are provided in legislation (e.g. EU, 2002, EU, 2008), standards (ISO, 2002, BSI, 2009) and scientific articles (King et al., 2006, Paterson et al., 2016).…”
Section: Towards a Classification Of Different Types Of Reusementioning
confidence: 99%
“…Aiming at the damaged or aging truck crane, the carbon fiber reinforced remanufacturing technology is selected to repair the high strength steel jib structure. The strengthening method of truck crane jib structure is composed of five parts, including surface treatment, fiber placement, resin ratio, low pressure infusion and resin curing.…”
Section: Fatigue Dangerous Position Of Jib Structure For Remanufacturmentioning
confidence: 99%
“…Remanufacturing is both established terminology and an established process, but is on occasion used ambiguously. Consider [28], who identified literature which fails to separate remanufacturing from refurbishing and recondition or [16], who found that remanufacturing in the aerospace industry is sometimes referred to as rebuilding.…”
Section: Remanufacturing Definitionmentioning
confidence: 99%
“…Given that recycle, reuse and remanufacturing are understood as separate processes within literature [17,21,23,[26][27][28][29][30] and noting that literature's opinion or viewpoint is formed by studying operations conducted within industry, it is important to remain consistent with existing litearture. However, it has thus far been shown that remanufacturing has potentially a presence in recycle and reuse, which are both recovery operations of the ELV directive.…”
Section: Establishing Remanufacturing As a Stand Alone Strategymentioning
confidence: 99%